Optimizing opportunity into innovation: a case study on a student entrepreneur - an ice cream innovator / Junainah Junid ... [et al.] - Junid, Junainah; Rosly, Hardi Emrie; Rahim, Hardy Loh; Mohd Lajin, Noor Faizah (2018)
This paper is about a student entrepreneur in a Malaysian university that chose entrepreneurship as a career. What started as a hobby in school inspired her to develop and expand her interest into a full-fledged business. This case study discusses a business owned by Liyana who is active inside and outside of the university, demonstrating the will and effort in taking advantage all of the support systems available to her which turned her into an innovator. The purpose of this study is to present the entrepreneurial competencies that lead an individual into becoming a student entrepreneur who then turned innovator. Her competencies are described to give a feel of how entrepreneurial competencies help a student's business become successful while being a successful student as well. The researchers went for an in-depth interview to gather data to produce a case study of the business. The first part of the paper will introduce the student's profile and later it will discuss on innovation and value proposition to ensure competitive advantage of the business also with the main strategy taken to ensure business growth. Finally, this paper will also evaluate Liyana's actions from the Personal Entrepreneurial Competencies (PEC) perspective.